Identification of the active principles of black mashua (Tropaeolum tuberosum) and the effect of the production process of a mixed drink of mashua and pineapple - Feliciano-Muñoz, Osiris (2021)
The current trend is to consume natural products with functional properties that reduce the risk of developing several types of diseases. One of the foods that meets these characteristics is mashua (Tropaeolum tuberosum), since it is an important source of bioactive compounds such as anthocyanins, glucosinolates and phenols. This feature is especially distinctive in purple and black mashuas compared to the yellow ones, because they have higher antioxidant capacity and are rich in phenolic compounds. The purpose of this research is to identify the active principles of black mashua, as well as to elaborate a mixed drink of mashua and pineapple (Golden variety) and to study the effect of the production process on the conservation of these active principles in the mixed drink.